Poder local e gestão do sistema de ensino básico em Pinheiros-ES: possibilidades e desafios na região contestada (2001 – 2016) - Lisboa, Héryca da Silva (2019)
The aim of this research is to analyze some aspects of the Management of the Education System of the Municipality of Pinheiros-ES between 2001 and 2016 through documents that expose SEME's conduct in organizing the areas of Basic Education under its responsibility. Therefore, it is investigated in which ways PDE adherence occurs and how the resources management of FNDE and FUNDEB works. It is highlighted the progression and achievement of learning goals through IDEB indicators. The organization of appointments of Secretaries of Education, the choice of school leaders, and staff competitions are evaluated. The institution of the Education Council and the Municipal Education System is questioned. Some implications are also indicated due to the elaboration and approval of the Position and Salary Plan of the Municipal Teaching Staff. The dilemmas and regional struggles are considered to have triggered characteristics that were peculiarly perpetuated in the local history, hindering the institutionalization of Democratic Management. This Municipality is located in the extreme north of the state of Espírito Santo in the area that was disputed with the State of Minas Gerais, an issue that although resolved in 1963, through a treaty between the two federative units, left deep marks on the political culture of the region, such as the established patrimonialism and clientelism, especially in the way of conducting the management policy that presents itself in a situation of certain anomie, this term is used by Durkheim to denote the absence or loosening of the social order. Because it was held in light of the perspective based on cultural history in an understanding that sources need to be interrogated in order to speak for themselves, it was sought to dialogue with the ideas of Ginzburg and Bloch to support the bibliographic and documentary research. The results of the study demonstrate that the political-educational programs – provided for by the 1988 Constitution and LDB 9394/96, which are increased by other legal provisions – have had many difficulties in establishing themselves as State policies in the Municipality, because they run into impediments directly related to the local political culture. And in this case, there is a predominance of serving individual and particular interests over systematic political actions aimed at the common good, thus undermining the development of Democratic Management and preventing community participation from happening actively and effectively in political educational and teaching decisions in Pinheiros-ES.